Uncertainty and hope in people with metastatic uveal melanoma in the era of immunotherapy and targeted treatments: a theory-based qualitative study - Tim Luckett; Carrie-Anne Ng; Julia Lai-Kwon; Damien Kee; Brendan Mulhern; Anthony M. Joshua (BMC Cancer)
Abstract Background The advent of immunotherapies and targeted treatments has improved survival for some people with metastatic cancer but also increased prognostic uncertainty. To inform clinician-patient communication and supportive care, this study explored uncertainty-related coping among people with metastatic uveal melanoma (mUM) – a disease for which treatments have emerged especially suddenly. Methods A qualitative approach was taken using semi-structured interviews. Participants with mUM were recruited through consumer organisations internationally. Interviews explored participant perspectives on the impacts of uncertainty and their related coping strategies. Analysis involved inductive coding followed by deductive coding against Mishel’s (1988) theoretical framework of uncertainty in illness. Results Seventeen people participated, including 10 from Australia. Participants described experiencing uncertainty as disempowering but also leveraged the opportunity it presented for remaining hopeful. Some participants used meta-cognition– alluded to as ‘tricking’ or ‘fooling’ themselves - to manage inconsistency between hoping for an exceptional response and accepting that benefits were likely to be modest at best. Most participants were able to maintain everyday normalcy but struggled to discuss their illness and treatment with family and friends. Participants reported heightened anxiety in the lead-up to routine scans and while awaiting results. Conclusions Coping with uncertainty in the era of immunotherapy and targeted treatments involves ‘hoping for the best while preparing for the worst’. Supportive care is especially needed at the time of scans. Some patients may also benefit from help with talking to their social networks. Head-to-head comparisons are needed of differing psychological interventions.